2010
DOI: 10.1128/aem.01067-10
|View full text |Cite
|
Sign up to set email alerts
|

Effective Gene Silencing in a Microsporidian Parasite Associated with Honeybee ( Apis mellifera ) Colony Declines

Abstract: Honeybee colonies are vulnerable to parasites and pathogens ranging from viruses to vertebrates. An increasingly prevalent disease of managed honeybees is caused by the microsporidian Nosema ceranae. Microsporidia are basal fungi and obligate parasites with much-reduced genomic and cellular components. A recent genome-sequencing effort for N. ceranae indicated the presence of machinery for RNA silencing in this species, suggesting that RNA interference (RNAi) might be exploited to regulate Nosema gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
91
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 38 publications
7
91
0
2
Order By: Relevance
“…Since its discovery in Caenorhabditis elegans (Fire et al 1998), RNAi has become the predominant reverse genetic method in a variety of non-model organisms. Moreover, as honeybees are among the few recognized beneficial insects with a large economical and ecological impact, the use of RNAi is increasingly used as a tool for fighting pests and pathogens in apiculture (Maori et al 2009;Paldi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in Caenorhabditis elegans (Fire et al 1998), RNAi has become the predominant reverse genetic method in a variety of non-model organisms. Moreover, as honeybees are among the few recognized beneficial insects with a large economical and ecological impact, the use of RNAi is increasingly used as a tool for fighting pests and pathogens in apiculture (Maori et al 2009;Paldi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dicer expression was indeed suppressed after siRNA treatment for the first two days post infection. It is necessary to point out that N. ceranae is an intra-cellular parasite and the honey bee RNA interference pathway could also be activated to suppress N. ceranae gene expression, as suggested from previous study [21]. It is unknown whether honey bees use the siRNA to target the parasite gene Dicer or the parasite used the siRNA to silence the expression level of its own Dicer.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is no functional analysis of Dicer in N. ceranae. It is also unclear whether N. ceranae possesses a functional RNA interference pathway, although prior work has indicated that growth of this parasite is inhibited by RNAi [21]. In order to determine the importance of N. ceranae Dicer for its reproduction, we designed small interfering RNA (siRNA) to target the parasite gene for Dicer.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement, oral administration of dsRNA appears to be effective at regulation of gene expression in honey bees. [69][70][71][72][73][74][75][76] In addition, high dose injection of dsRNAs into the hemocoel has been used for delivery and inhibition of target genes in multiple tissues in this species [77][78][79][80][81][82][83][84][85][86] independent of the site of injection, demonstrating that these molecules can be efficiently taken up by disparate tissues once in the open circulatory system. Our results, in conjunction with the previous studies using dsRNA in other insect species, suggest that uptake of longer dsRNAs may be more efficient than shorter miRNAs.…”
Section: Discussionmentioning
confidence: 99%